“Estudio de la viabilidad de la semilla de algodón en las variedades (inia 802 shanao, gossypium barbadense,inía 801 bja 594, gossypium hirsutum ) bajo métodos de almacenamiento, natural y artificial” - Alarcón Torres, Justimiano (2008)
In this research working is evaluated two varieties of cotton; INIA 801 BJA 594 and INIA 802 "Shanao" ;under two methodes of storage:natural and cold camera. The working was made in the Laboratorys lnstallations of the Regional committee from San Martin, Region San Martin -the main objectives were; evaluate under Laboratory conditiones the physiological behavior of the germinations of cottons sedes in the varieties INIA 801 BJA 594 and INIA 802 "Shanao", under conditions of natural storage and artificial and determine what is the main method of storage which permits to determine theviable of the cottons sedes under the studious treatments. The desing used was a; Complete Design Randomizado with a factorial arragment of 2x2x6 adapting a total of 24 treatments; being the variet y INIA 801 under natural conditions and cold camera which had the best results with percents of 93% and 94% in elation of percents of germinations respectively.